2021
DOI: 10.3233/jpd-202421
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pathways of LRRK2-G2019S/Rab10 Interaction in Dopaminergic Neurons

Abstract: Background: Inherited mutations in the LRRK2 protein are the common causes of Parkinson’s disease, but the mechanisms by which increased kinase activity of mutant LRRK2 leads to pathological events remain to be determined. In vitro assays (heterologous cell culture, phospho-protein mass spectrometry) suggest that several Rab proteins might be directly phosphorylated by LRRK2-G2019S. An in vivo screen of Rab expression in dopaminergic neurons in young adult Drosophila demonstrated a strong genetic interaction b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
(99 reference statements)
3
8
0
Order By: Relevance
“…The surfaces of Rab29 and Rab10 predicted to interact with LRRK2 had almost identical interface residues, which is consistent with previous work suggesting that Rab10 interacts with LRRK2 at the Rab29 site (33). Rab5A, 5B, and 5C, which can be phosphorylated by LRRK2 (34), contain an alanine in the position corresponding to Asp 43 in Rab29 (fig. S2H).…”
Section: Rab29-dependent Recruitment Of Lrrk2supporting
confidence: 89%
See 1 more Smart Citation
“…The surfaces of Rab29 and Rab10 predicted to interact with LRRK2 had almost identical interface residues, which is consistent with previous work suggesting that Rab10 interacts with LRRK2 at the Rab29 site (33). Rab5A, 5B, and 5C, which can be phosphorylated by LRRK2 (34), contain an alanine in the position corresponding to Asp 43 in Rab29 (fig. S2H).…”
Section: Rab29-dependent Recruitment Of Lrrk2supporting
confidence: 89%
“…6B), suggesting that membrane recruitment of LRRK2 is sufficient to activate Rab10 phosphorylation without a requirement for tetramerization. Rab10 phosphorylation and Ser 1292 autophosphorylation are thus independent molecular events during LRRK2 signaling ( 42 , 43 ). Endogenous Rab38 was also reported to increase Rab10 phosphorylation but not Ser 1292 autophosphorylation in melanocytes ( 44 ).…”
Section: Rab29–lrrk2 Tetramer and Rab29-dependent Activationmentioning
confidence: 99%
“…Investigating the range of varying gene expression levels through mass spectrometry analysis, we have identified several genes which were commonly altered at all time points after α-syn PFF injection, including TPPP3 and RAB10, which were upregulated, and CAMK2A and DYNLL1, which were downregulated. These results agree with prior reports on neurodegenerative diseases, where all four genes displaying association with not only Parkinson’s (Simunovic et al, 2009; Zhang et al, 2014; Olah et al, 2020; Fellgett et al, 2021), but also with Alzheimer’s (Kong et al, 2009; Ghosh and Giese, 2015; Ridge et al, 2017; Singh et al, 2022) disease. Thus, while we may conclude that these genes may serve as potential biomarkers for early detection of general neurodegeneration, it appears difficult to assign them to a particular diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…Rab10, one of the best-characterized substrates for Lrrk2, mediates several of Lrrk2’s cellular functions [41]. In Drosophila , Rab10 and Lrrk2-G2019S synergistically affect the activity of dopaminergic neurons, mediating deficits in movement [59, 60]. We have shown that WGE treatment downregulated levels of Lrrk2 accumulation and phosphorylated Rab10 (Fig.…”
Section: Discussionmentioning
confidence: 92%